Extending the yarning yarn: Collaborative Yarning Methodology for ethical Indigenist education research - Shay, Marnee (The Australian Journal of Indigenous Education, 2019)
Abstract Yarning scholarship is emerging in the Australian context. There are a growing number of Indigenous scholars who advocate for using yarning in research and this paper aims to contribute to this methodological discussion. In this paper, I outline the development of a methodology, which I have named Collaborative Yarning Methodology (CYM). CYM extends on the current yarning scholarship available to researchers through critically addressing the issue of data collection and analysis. The methodology was developed in undertaking my doctoral study in alternative school settings. In developing CYM, I discuss and analyse the implications of using Indigenous methodologies in institutionalised education settings and some of issues that may arise, and some explicitly for Indigenous researchers. Through analysing the current discourses that exists when undertaking Indigenous-focused research in education institutions, there are clearly connections in how Indigenous people are positioned politically, racially and socially when assuming the role of a researcher. I propose that in Indigenous education focused research, there continues to be an over-reliance of positivist ways of collecting yarning data, such as audio recording. I offer an alternative to audio recording, which incorporates collaborative approaches to data collection with participants underpinned by the principle of self-determination.